ENLIGHTENING THE CLOUD COMPUTING DOMAIN - Kaur, AmanPreet; Singh, Dr. Dheerendra (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Cloud computing is an emerging model of â€œcomputing as utilityâ€ to provide convenient, on demand access to shared pool of resources. In this paper, this grooming technology is presented in terms of its basic characteristics, services provided, models, and why cloud computing is a widely accepted in business and software enterprises.